The Influence of Ummi Method Using Mother Tongue Approach on Arabic Reading Skills - Winda Maghfira Yuliana; Mia Nurmala; Yayan Nurbayan (Universitas Cokroaminoto Palopo, 2024)
Students’ reading skills depend on their teacher and effective teaching methods are crucial, especially for Arabic language teachers. The Ummi method designed for learning to read the Quran is easy and enjoyable. The Ummi method can be applied to teaching reading in Arabic because the language used in the Quran is Arabic. The Ummi method has three mother tongue approaches: the Direct method, Repetition, and Affection. This study employs a quantitative approach with a quasi-experimental, non-equivalent control group design. The research population includes students from SMP Laboratorium Percontohan UPI Bandung, with purposive sampling techniques. Class VII-C is the experimental sample, while Class VII-D is the control sample. Data collection involved observation, interviews, pre-tests, and post-tests. The main objective of this research is to demonstrate the effect of the Ummi method through the mother tongue approach, on the skills of reading Arabic texts. The hypothesis test result showed a significance value of 0.009<0.05, which rejects Ho and accepts Ha. The experimental class had a mean gain score of 23.4531, higher than the control class’s 13.9219. It was concluded that the Ummi method through the mother tongue approach, significantly improves Arabic reading skills.